Success?: ESDP military conflict management operations: 2003-2009 - Rodt, Annemarie Peen (2009)
From 2003 to 2009, the EU launched five military conflict management operations within the framework of the European Security and Defence Policy. This thesis examines their success. To this end, the thesis develops a definition and a set of criteria for success. It applies this theoretical framework in an empirical case study of success in the five EU operations, which were undertaken in Macedonia, Bosnia and Herzegovina, the Democratic Republic of Congo, Chad and the Central African Republic. Having established the level and nature of their success, the thesis goes on to examine the conditions under which ESDP military conflict management operations can be successful. The key finding of the research is that for an operation of this nature to succeed, it is necessary that it secures sufficient support internally, within the EU, and externally, outside the EU, from domestic, regional and international actors involved in the conflict and its management.